Development of a new drug candidate for the inhibition of Lassa virus glycoprotein and nucleoprotein by modification of evodiamine as promising therapeutic agents - Akash, Shopnil; Baeza, Javiera; Mahmood, Sajjat; Mukerjee, Nobendu; Subramaniyan, Vetriselvan; Islam, Md. Rezaul; Gupta, Gaurav; Rajakumari, Vinibha; Chinni, Suresh V.; Ramachawolran, Gobinath; Saleh, Fayez M.; Albadrani, Ghadeer M.; et al. (Frontiers in Microbiology, 2023)
The Lassa virus (LASV), an RNA virus prevalent in West and Central Africa, causes severe hemorrhagic fever with a high fatality rate. However, no FDA-approved treatments or vaccines exist. Two crucial proteins, LASV glycoprotein, and nucleoprotein, play vital roles in pathogenesis and are potential therapeutic targets.As effective treatments for many emerging infections remain elusive, cutting-edge drug development approaches are essential, such as identifying molecular targets, screening lead molecules, and repurposing existing drugs. Bioinformatics and computational biology expedite drug discovery pipelines, using data science to identify targets, predict structures, and model interactions. These techniques also facilitate screening leads with optimal drug-like properties, reducing time, cost, and complexities associated with traditional drug development. Researchers have employed advanced computational drug design methods like molecular docking, pharmacokinetics, drug-likeness, and molecular dynamics simulation to investigate Evodiamine derivatives as potential LASV inhibitors. Results reveal remarkable binding affinities, with many outperforming standard compounds. Additionally, molecular active simulation data suggests stability when bound to target receptors. These promising findings indicate that Evodiamine derivatives may offer superior pharmacokinetics and drug-likeness properties, serving as a valuable resource for professionals developing synthetic drugs to combat the Lassa virus.